2022
DOI: 10.3390/ijerph19116529
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microbial Communities in Wastewater Treatment Plants Containing Heavy Metals Located in Chemical Industrial Zones

Abstract: Water pollution caused by heavy metals (HMs) poses a serious risk to human health and the environment and can increase the risk of diabetes, cancer, and hypertension in particular. In this study, two full-scale wastewater treatment plants (WWTPs) in industrial zones in southern China were selected to analyze the microbial community structure, diversity, similarity, and differentiation in the anoxic/oxic (AO) and anoxic/oxic membrane bioreactor (AO-MBR) units under the stress of HMs. High-throughput sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Saprospirales can indeed be found in various environments, such as saline water, freshwater, soil, bioreactors, and wastewater treatment plants, as has been already mentioned in various studies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In addition, air, plants, as well as terrestrial and saline water hosts are also potential environments for Saprospirales.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Saprospirales can indeed be found in various environments, such as saline water, freshwater, soil, bioreactors, and wastewater treatment plants, as has been already mentioned in various studies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In addition, air, plants, as well as terrestrial and saline water hosts are also potential environments for Saprospirales.…”
Section: Discussionmentioning
confidence: 76%
“…Bacteria belonging to Saprospirales can be found in natural ecosystems such as marine and freshwater environments, and soils [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Furthermore, several studies have reported that Saprospirales members can be found in wastewater treatment plants, and especially in activated sludge and anaerobic ammonium oxidation reactors [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Regarding the latter, hydrolysis of proteins, denitrification, aromatic compound degradation, and organic matter decomposition are confirmed capabilities of certain bacteria belonging to the order Saprospirales [ 30 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is noteworthy that there were heterotrophic microorganisms present in the biomass that are involved in the nitrogen cycle. For example, Haliangium and Comamonas (2.4 and 2.5% of the total reads in TCMCRWS, respectively) are aerobic heterotrophic capable of NO 2 – reduction, , while members of the family Gemmataceae (1.25% of the total reads in TCMCRWS) can be N 2 O-reducing organisms …”
Section: Resultsmentioning
confidence: 99%
“…For example, Haliangium and Comamonas (2.4 and 2.5% of the total reads in TCMCRWS, respectively) are aerobic heterotrophic capable of NO 2 − reduction, 52,53 while members of the family Gemmataceae (1.25% of the total reads in TCMCRWS) can be N 2 O-reducing organisms. 54 The sum of the relative abundances of the putative AOB (Nitrosomonas and Nitrosospira, etc.) and NOB taxa (Nitrospira and Nitrotoga) were estimated from the microbial composition profiles (Figure 3a,b).…”
Section: Overall Microbial Community Trendsmentioning
confidence: 99%
“…Other than organic wastes, Proteobacteria and Bacteroidetes were also found in wastewaters with high heavy metals. The most abundant phyla in wastewater treatment plants containing heavy metals located in chemical industrial zones for all the samples are Proteobacteria, Chloroflexi, Actinobacteriota, Bacteroidetes, and Planctomycetes, in the order of their relative proportions (Zeng et al 2022). Proteobacteria, Bacteroidota, Patescibacteria, and Chloroflexi were the dominant phyla from active sludge in China's tropical municipal wastewater treatment plant (Gu et al 2022).…”
Section: Taxonomic and Abundance Of Bacteria In Pomsementioning
confidence: 97%